AFFORDABLE COFFEE-TO-GO AS A LIFESTYLE AMONG GENERATION Z AND CONSUMER LEGAL AWARENESS IN MAKASSAR - Siti Syarifah Wafiqah Wardah; Syarifuddin Syarifuddin; Intan Permatasari (Universitas Negeri Makassar, 2026)
The rapid growth of Indonesia’s coffee industry has encouraged the emergence of affordable coffee-to-go products that are widely consumed by Generation Z in urban areas. This phenomenon reflects a shift in coffee consumption from merely fulfilling caffeine needs to becoming part of a contemporary lifestyle. This study aims to analyze the meaning of affordable coffee-to-go in the lives of Generation Z in Makassar, identify the factors influencing their consumption decisions, and explore their level of consumer legal awareness in everyday consumption practices. This research employed a qualitative descriptive approach with data collected through semi-structured interviews with Generation Z consumers aged 18–25 years who regularly consume coffee-to-go products priced between Rp10,000 and Rp20,000. The data were analyzed using thematic analysis to identify key patterns and themes emerging from participants’ experiences. The findings show that affordable coffee-to-go is perceived not only as a practical beverage supporting daily mobility but also as a source of energy to enhance focus and as part of the social lifestyle of young people. Consumption decisions are mainly influenced by product affordability, practicality, and the influence of social environments and digital media. Although most participants demonstrate a basic understanding of consumer rights, particularly regarding product safety and information transparency, their attention to formal consumer protection aspects remains limited. This study contributes to the development of consumption sociology and consumer awareness studies while providing practical insights for improving consumer protection literacy among Generation Z.